2022
DOI: 10.9734/ijecc/2022/v12i1130955
|View full text |Cite
|
Sign up to set email alerts
|

Terminal Heat Stress and Its Mitigation Options through Agronomic Interventions in Wheat Crop: A Review

Abstract: Climate change will be one of the most critical dangers to agriculture in the coming years. On average, abiotic stresses account for 50% of the production losses in agricultural production. Terminal stress is a major environmental issue limiting wheat production in the majority of wheat-growing regions across the world. The term "terminal heat stress" refers to a rise in temperature (> 30°C) after anthesis during grain development which impairs the process of grain filling in wheat. Rising temperatures shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…As for the second late date, the conditions that were available on the first date did not provide for him, so the temperatures and the intensity of the lighting increased, so the metabolic processes decreased, and therefore the nutrients collected in the grains in the form of starch decreased, and the carbohydrate content decreased. This is in agreement with [59,64] , who indicated that higher temperatures during grain filling accelerate plant growth, leading to a short filling period, and higher temperatures during this critical period affect grain size and weight due to lack of starch formation. of metabolites and thus low carbohydrate content [65] , confirmed that the late agricultural dates have negative effects, including high temperatures during the grain filling period, which reduces the accumulation of nutrients resulting from the process of food building in the grains.…”
Section: Carbohydrate Content (%)supporting
confidence: 92%
“…As for the second late date, the conditions that were available on the first date did not provide for him, so the temperatures and the intensity of the lighting increased, so the metabolic processes decreased, and therefore the nutrients collected in the grains in the form of starch decreased, and the carbohydrate content decreased. This is in agreement with [59,64] , who indicated that higher temperatures during grain filling accelerate plant growth, leading to a short filling period, and higher temperatures during this critical period affect grain size and weight due to lack of starch formation. of metabolites and thus low carbohydrate content [65] , confirmed that the late agricultural dates have negative effects, including high temperatures during the grain filling period, which reduces the accumulation of nutrients resulting from the process of food building in the grains.…”
Section: Carbohydrate Content (%)supporting
confidence: 92%
“…Wheat will be negatively impacted by warming temperatures in India, and one way to reduce this negative impact is by sowing wheat earlier (Kalra et al 2008, Balwinder-Singh et al 2015, Dubey et al 2020, Nesar et al 2022. Despite the importance of early sowing, many farmers sow wheat late in the eastern IGP, past the optimal date of November 25th recommended by agronomists (Sattar et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Heat tolerance mechanisms in cultivars have rendered them less vulnerable to heat stress, and these cultivars were found to have a smaller decline in the performance index (Balla et al 2021). The heat stress at the end of the season, on the one hand, by accelerating the rate of growth and development and shortening the duration of the vegetative and reproductive period of the plant (Nesar et al 2022;Ullah et al 2022), and on the other hand, with a negative effect on the optimal development of grain induced by severe oxidative damage (Qaseem et al 2019), causes a decrease in yield. According to the results of this research, the combined study of phenological and morphological traits is important in evaluating the heat tolerance of cultivars and their investigation is recommended.…”
Section: Discussionmentioning
confidence: 99%